2023
DOI: 10.21203/rs.3.rs-2462664/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Gut microbiota aggravates neutrophil extracellular traps-induced pancreatic injury in hypertriglyceridemic pancreatitis

Abstract: Hypertriglyceridemic pancreatitis (HTGP) is featured by higher incidence of complications and poor outcomes. Dysbiosis of gut microbiota has been established in HTGP, the impact of gut microbiota in pancreatic injury remains unclear. We observed that HTGP patients’ gut microbiota involved lower diversity and loss of beneficial bacteria, which were negatively correlated with local and systemic complications. In FMT mouse model, colonization with gut microbiota from HTGP patients exacerbated pancreatic injury th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Moreover, Li et al. reported that dysbiosis is associated with neutrophil extracellular traps‐induced pancreatic injury, which is a risk factor for pancreatic cancer 26 …”
Section: Pathogenesis Of Pancreatic Carcinogenesis In Patients With N...mentioning
confidence: 99%
“…Moreover, Li et al. reported that dysbiosis is associated with neutrophil extracellular traps‐induced pancreatic injury, which is a risk factor for pancreatic cancer 26 …”
Section: Pathogenesis Of Pancreatic Carcinogenesis In Patients With N...mentioning
confidence: 99%